Khazanah Tafsir Di Nusantara: Penelitian terhadap Tokoh dan Karyanya di Malaysia, Brunei Darussalam, Singapura, dan Thailand - Abdullah, Mustaffa bin (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
Indonesian archipelago is a rich teritory for any kinds of knowledge left by previous theologian. However that treasury is careless from society and local examiner. This treasury is used by west examiners as William Roff, Broki, Peter Riddell and other. West bachelor wich do some... to explor Indonesian treasury. But this writingwill explore and discribe somefigures and their though from Malaysia, Brunai Darussalam, Singapore and Thailand.